36: RIO GRANDE TURKEY MIGRATIONS AS RELATED TO HARVEST REGULATION IN TEXAS* - Jack Ward Thomas; Rodney G. Marburger; Calvin Van Hoozer (Wildlife Society Bulletin)
ABSTRACT Rio Grande turkeys (Meleagris gallopavo intermedia) on the Edwards Plateau in Texas made annual migrations averaging 10.9 air‐line miles between the farthest known points (53 records of movement indicated that range was 3.5 to 26.0 miles for 310 turkeys marked during 1961‐1963). All turkeys returned to the winter areas where they had been marked. All land is privately owned, and hunting rights are rigidly controlled. The present November‐December hunting season occurs when turkeys are in winter concentrations, so access to them by hunters is controlled by a few landowners. This leads to underharvest, with only 4 percent of the birds taken annually. One method of increasing the harvest would be to hold a spring gobbler season, which would take place when turkeys are widely dispersed, when access to them is controlled by more landowners, and when they are available to more hunters. Hens should also be legal game in the fall in years of high populations. The socioeconomic factors involved, rather than the biological aspects of winter feeding, complicate the attainment of the proposed change in regulations. The importance of income from leased hunting rights and the use of winter feeding programs make changing difficult.